PWE-363 Bowelscope- results from the pilot sites. (22nd June 2015) - Neilson, LJ; Bevan, R; Nickerson, C; Patnick, J; Loke, R; Saunders, BP; Stebbing, J; Tighe, R; Veitch, A; Rees, CJ
Abstract : Introduction: A large UK study of single flexible sigmoidoscopy with adenoma clearance in patients aged 55–64, demonstrated a reduction in CRC incidence by 23% and mortality by 31% in intention-to-treat analyses. 1 This provided the rationale for provision of a new arm of the Bowel Cancer Screening Programme (BCSP), offering a single flexible sigmoidoscopy (FS) to all 55 year olds in England, known as BowelScope screening. BowelScope was introduced to 6 pilot sites, beginning in May 2013. It is to be rolled out across the country by 2016. Method: We aim to describe the findings, in terms of procedural data, from the first year of BowelScope screening at the pilot sites. Data were obtained from the Bowel Cancer Screening System database for all participants who underwent FS between May 2013–May 2014. Procedural data were recorded, including entonox use, adenoma detection rate (ADR), cancer detection, complications and colonoscopy conversion rates. Results: Overall uptake was 44.1%. 1 cancer was detected. Mean ADR was 9.2%. The mean number of patients requiring colonoscopy conversion was 4.2%. Mean complication rate was 0.1%, including bleeding, discomfort, difficult polyp excision and unwell patient. There was wide variation in entonox use. (Table 1 ). Conclusion: Uptake has improved since the six month data were presented but remains lower than for the FOB arm of the BCSP, and varies between sites. The ADR is 9.2% (range 7.6% - 11.1%). This is lower than reported in the UK FS screening trial (12.1%) 1, however ADR calculations in BowelScope do not include adenomas not removed at FS but removed later at colonoscopy, whereas the FS trial did. The ADR is comparable to the BowelScope pathfinder project (9.6%). 2 Further work is necessary to explore the variation in uptake rates. Variation in ADR exists between centres. Further analysis of endoscopist factors and patient groups may explain this. Entonox use varies widely but does not appear to correlate with ADR- further work may be required to investigate this. Disclosure of interest: None Declared. References: Atkin WS et al . Lancet 2010;375:1624–33 Bevan R et al . Endoscopy 2015;47(3):225–31